Liebe Leserin, lieber Leser (Balint Journal, 2017)
Aus den drei prämierten Arbeiten für den Internationalen Studenten Balint Preis finden Sie nachstehend eine Leseprobe:I learnt the importance of practicing patient-centred medicine – of avoiding the tendency to reduce people to numbers and trends, and treating them as people with individual experiences of illness. All the communication workshops I had on demonstrating empathy and active listening suddenly became very relevant throughout my journey with Margaery.